Menerima Instagram Apa Adanya: Melacak Pemaknaan dan Fantasi Individu Pelaku Aktivitas Kerja Sebagai Admin terhadap Aplikasi Media Sosial Instagram - Hanz Sinelir (Retorik: Jurnal Ilmu Humaniora, 2022)
After the birth of the internet, the relationship between humans and technology is often discussed academically in two poles, namely utopia and dystopia. This study uses examples from the popular social network platform Instagram to find out how users interpret their relationship with technology. The subjects in the study were Instagram account admins, either from commercial brands or social movements. The job of an "Instagram admin" is a new job that requires media literate subjects, who are expected to be able to provide insights on the tug-of-war debate about the relationship with technology. This study uses the concept of fantasy, which is closely related to the formation of the subject in Lacanian psychoanalysis, and is also based on the concept of virtuality by Pierre Lévy. The method used in this study is new ethnography combined with clinical psychoanalysis. The main argument of this research is that Instagram works in the subconscious of its users to cover up castration. This is shown when Instagram (and activities on it) presents language in the form of features and algorithms that exhibit dislocation, continuity, experimentation, and affirmation. Under this condition, what transpires is a sado-masochistic interactivity owing to the failure to recognize the space and rules provided by Instagram. This situation causes anxiety, which in turn generates for the users a relation to fantasy ($◊a). For the admins of Instagram accounts, the process is undergone during their work. By having a fantasy ($◊a), admins gain the possibility to interpret Instagram according to what they desire in life.